Excerpts from the author’s works - Aguilera, Juan Luís (Romano džaniben, 2021)
A collage of texts introduces the work and life of a Romani poet Juan Luís Aguilera: a foreword written by Ismael Cortés Gómez for the book of poems by J. L. Aguilera in preparation, a prologue by Aguilera´s son, and a short biographical text are followed by Czech translation of selected poems. Initiated by the editor of the book in preparation, several of the poems were selected for translation into northcentral Romani by a Czech Romani writer Eva Danišová.